Combination of ultrasound guided superficial cervical plexus block and local infiltration for oromaxillofacial surgeries: a case series - Zhao, Hao-ran; Hao, Jian-shuai; Xue, Ling-fa; Zhao, Jin-ze; Wang, Yi-chen; Xiao, Wen-lin (Frontiers in Oncology, 2024)
IntroductionWhen elderly patients have underlying diseases combined with oromaxillofacial diseases requiring surgical treatment, the application of conventional general anesthesia (GA) for oromaxillofacial surgical diseases has become a risk due to underlying disease reasons. The objective of this study was to evaluate the efficacy and safety of ultrasound-guided superficial cervical plexus block (SCPB) anesthesia combined with local infiltration anesthesia (LIA) for partial oral and maxillofacial surgery (OMFS) in patients who with risk for GA due to underlying disease.MethodsThe clinical data of 7 high risk patients with OMFS treated with SCPB anesthesia combined with LIA were retrospectively analyzed. All seven surgeries were performed on one side of the neck. All patients were given ultrasound-guided SCPB anesthesia by the same anesthesiologist, LIA by the same surgeon, and surgery was performed under continuous Electrocardiogram (ECG) monitoring.ResultsSeven patients had stable vital signs and no significant postoperative complications. The results of this study indicated that SCPB anesthesia combined with LIA is a safe and effective anesthesia technique with a high success rate and patient tolerance.DiscussionFor patients with OMFS who have a risk for GA due to underlying diseases, ultrasound-guided cervical superficial plexus block anesthesia combined with LIA is a safe and effective alternative to conventional GA.